Promising and Eco‐Friendly Cu2X‐Based Thermoelectric Materials: Progress and Applications - Liu, Wei‐Di; Yang, Lei; Chen, Zhi‐Gang; Zou, Jin (Advanced materials (Weinheim), 2020)
Due to the nature of their liquid‐like behavior and high dimensionless figure of merit, Cu2X (X = Te, Se, and S)‐based thermoelectric materials have attracted extensive attention. The superionicity and Cu disorder at the high temperature can dramatically affect the electronic structure of Cu2X and in turn result in temperature‐dependent carrier‐transport properties. Here, the effective strategies in enhancing the thermoelectric performance of Cu2X‐based thermoelectric materials are summarized, in which the proper optimization of carrier concentration and minimization of the lattice thermal conductivity are the main focus. Then, the stabilities, mechanical properties, and module assembly of Cu2X‐based thermoelectric materials are investigated. Finally, the future directions for further improving the energy conversion efficiency of Cu2X‐based thermoelectric materials are highlighted. Deriving from their high performance and eco‐friendliness, superionic Cu2X‐based thermoelectric materials are attracting ever‐increasing attention. A comprehensive summary of the understanding of the superionicity, performance enhancement strategies, and material stability design can set up a solid foundation for future development. Pointing out the development challenges can better guide future studies.